Analisis Pelatihan dan Pengembangan Sumber Daya Manusia dalam Kafe Sakera Telang Berbasis Kompetensi - M. Hotib Jailani; Mudji Kuswirno (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This research entitled " Analysis of Competency-Based Training and Development of Sakera Telang Café Human Resources " uses qualitative description research methods by conducting field research. Field research is a scientific way to obtain valid data with the aim that can be developed, and proven through certain knowledge that can be used to understand, solve and anticipate problems in their fields. In the era of globalization and increasingly fierce business competition, the quality of human resources (HR) is one of the key success factors of an organization. Sakera Cafe, as one of the culinary industry players, faces similar challenges. Not all employees work earnestly, causing delays in work. Employee training and development not only aims to improve skills and knowledge, but also to motivate employees so that they can work more effectively and efficiently. These activities are expected to produce more competent employees, which in turn will contribute positively to the overall performance of the organization.